2018
DOI: 10.1590/0034-7167-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Death education: sensibility for caregiving

Abstract: the method was considered applicable and effective to achieve the objective, that is, it enables learners to act as protagonists of the teaching-learning process, building together a new perspective of end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
0
12
0
8
Order By: Relevance
“…Furthermore, they expressed a desire to repeat the initiative in the future. The hospice professionals confirmed that the education initiative motivated them to improve their knowledge and competencies in their everyday work, much in the way that other healthcare professionals undergo continual training to improve their relational competencies [ 35 , 58 , 59 ]. Indeed, they stated that this initiative allowed them to improve both their teamwork skills and their knowledge of themes related to death education.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, they expressed a desire to repeat the initiative in the future. The hospice professionals confirmed that the education initiative motivated them to improve their knowledge and competencies in their everyday work, much in the way that other healthcare professionals undergo continual training to improve their relational competencies [ 35 , 58 , 59 ]. Indeed, they stated that this initiative allowed them to improve both their teamwork skills and their knowledge of themes related to death education.…”
Section: Discussionmentioning
confidence: 95%
“…Photography has also been used in the reflective educational sphere (4)(5)(6)(7) , in order to create images and form knowledge about the social sphere. In that sense, there are studies that have used participatory photography or Photovoice.…”
Section: Introductionmentioning
confidence: 99%
“…The last major theme -regarding willingness to reimplement the intervention -revealed that participants were indeed interested in repeating the experience in the future. Participants believed that introducing similar death education interventions in high schools would be worthwhile partly because it would allow hospice professionals to improve their knowledge and relational competencies in their everyday work, much as other healthcare professionals do [46][47][48][49][50]. The hospice staff stated that this intervention allowed them to improve both their teamwork skills and their knowledge concerning themes related to death education.…”
Section: Discussionmentioning
confidence: 99%